PENGARUH KUALITAS AUDIT DAN OPINION SHOPPING TERHADAP PEMBERIAN OPINI GOING CONCERN - Wiwi Idawati; Michael Michael (Universitas Bunda Mulia, 2017)
The existence of the company has many problem cases such as Enron and second problems that lead to self-fulfilling prophecy does not disclose the auditor's going concern status. The purpose of this study was to examine and analyze the effect of audit quality and the opinion of shopping on the provision of going concern opinion.The research method to test the validity, reliability, classic assumption test and to test hypotheses with multiple linear regression method and data used are primary data collected through questionnaires with respondents of this study is the auditor who works in Public Accounting Firm (KAP) in the region Jakarta with a total population of 236 KAP. The results showed that there was a significant effect of audit quality and the opinion of shopping on the provision of going concern opinion simultaneously with a significance value of 0.000 and when analyzed by partial quality audit of the administration of going concern opinion has a significant influence with a value of 0.000 and opinion on the provision of opinion going shopping concerned have a significant influence of 0.22.Keywords: Quality Audit, Opinion Shopping, opini going concern.